Odpowiedź :
Odpowiedź:
a2012 = 404 ⅕
Szczegółowe wyjaśnienie:
a1 = 2
a11 = 4
a2012 = ?
Korzystam ze wzoru na ogólny wyraz ciągu arytmetycznego:
an = a1 + (n - 1) * r
a11 = a1 + (11 - 1) * r
4 = 2 + 10r
4 - 2 = 10 r
10r = 2 /:10
r = 2/10
r = ⅕
an = a1 + (n - 1) * r
a2012 = 2 + (2012 - 1) * ⅕
a2012 = 2 + 2011 * ⅕
a2012 = 2 + (2011)/5
a2012 = 2 + 402 ⅕
a2012 = 404 ⅕
a2012 = 404 ⅕
Szczegółowe wyjaśnienie:
a1 = 2
a11 = 4
a2012 = ?
Korzystam ze wzoru na ogólny wyraz ciągu arytmetycznego:
an = a1 + (n - 1) * r
a11 = a1 + (11 - 1) * r
4 = 2 + 10r
4 - 2 = 10 r
10r = 2 /:10
r = 2/10
r = ⅕
an = a1 + (n - 1) * r
a2012 = 2 + (2012 - 1) * ⅕
a2012 = 2 + 2011 * ⅕
a2012 = 2 + (2011)/5
a2012 = 2 + 402 ⅕
a2012 = 404 ⅕
Odpowiedź:
[tex]\large\boxed{\big a_{2012}=404\frac15}[/tex]
Szczegółowe wyjaśnienie:
[tex]a_n=a_1+(n-1)\cdot r\qquad czyli\quad a_{11}=a_1+10\cdot r[/tex]
Stąd:
[tex]4=2+10\cdot r\qquad/-2\\\\2=10r\qquad/:10\\\\r=\frac15[/tex]
[tex]\big a_{2012}=a_1+2011\cdot r\\\\ \big a_{2012}=2+2011\cdot \frac15=2+402\frac15=404\frac15[/tex]